Perinatal care in Western Uganda: Prevalence and factors associated with appropriate care among women attending three district hospitals. - Mercy Muwema; Dan K Kaye; Grace Edwards; Gorrette Nalwadda; Joanita Nangendo; Jaffer Okiring; Wilson Mwanja; Elizabeth N Ekong; Joan N Kalyango; Joaniter I Nankabirwa (PLoS ONE, 2022)
Background Perinatal mortality remains high globally and remains an important indicator of the quality of a health care system. To reduce this mortality, it is important to provide the recommended care during the perinatal period. We assessed the prevalence and factors associated with appropriate perinatal care (antenatal, intrapartum, and postpartum) in Bunyoro region, Uganda. Results from this study provide valuable information on the perinatal care services and highlight areas of improvement for better perinatal outcomes. Methods A cross sectional survey was conducted among postpartum mothers attending care at three district hospitals in Bunyoro. Following consent, a questionnaire was administered to capture the participants' demographics and data on care received was extracted from their antenatal, labour, delivery, and postpartum records using a pre-tested structured tool. The care received by women was assessed against the standard protocol established by World Health Organization (WHO). Poisson regression with robust standard errors was used to assess factors associated with appropriate postpartum care. Results A total of 872 mothers receiving care at the participating hospitals between March and June 2020 were enrolled in the study. The mean age of the mothers was 25 years (SD = 5.95). None of the mothers received appropriate antenatal or intrapartum care, and only 3.8% of the participants received appropriate postpartum care. Factors significantly associated with appropriate postpartum care included mothers being >35 years of age (adjusted prevalence ratio [aPR] = 11.9, 95% confidence interval [CI] 2.8-51.4) and parity, with low parity (2-3) and multiparous (>3) mothers less likely to receive appropriate care than prime gravidas (aPR = 0.3, 95% CI 0.1-0.9 and aPR = 0.3, 95% CI 0.1-0.8 respectively). Conclusions Antenatal, intrapartum, and postpartum care received by mothers in this region remains below the standard recommended by WHO, and innovative strategies across the continuum of perinatal care need to be devised to prevent mortality among the mothers. The quality of care also needs to be balanced for all mothers irrespective of the age and parity.